Encapsulation of betalain-rich extract from beetroot postharvest waste using a binary blend of gum Arabic and maltodextrin to promote a food circular bioeconomy - Mkhari, Tshamisane; Kaseke, Tafadzwa; Fawole, Olaniyi Amos (Frontiers in Nutrition, 2023)
The present study evaluated the potential of maltodextrin (MT), gum Arabic (GA), and their blends to produce functional beetroot waste extract powder (BWEP). The beetroot waste extracts were produced using 50% ethanol and encapsulated using 10% (1:10, w/v) of the GA and MT carriers at different blending ratios, namely, GA:MT 1:0, GA:MT 0:1, GA:MT 1:1, GA:MT 2:1, and GA:MT 1:2, respectively. The BWEP were analyzed for physicochemical, technofunctional, morphological, crystallinity, and antioxidant properties. BWEP produced using either GA or MT exhibited better colour, solubility, encapsulation efficiency, and betalain content. Powders from the blends of GA and MT showed better oil holding capacity and total phenolic content. On the other hand, powder yield, total soluble solids, titratable acidity, bulk density, and DPPH radical scavenging activity did not significantly differ (p>0.05) among the powders. BWEP produced using GA and MT separately was relatively smaller and more regular compared to the powders from the blended biopolymers. All powders showed signs of agglomeration, which was more pronounced in the powders from the blended biopolymers. A total of 16 metabolites, including betalains (9), phenolic acids (2), and flavonoids (5), were tentatively identified. The majority of the metabolites were entrapped in the BWEP produced using GA and MT separately. The quantified metabolites included gallic acid (33.62-44.83 µg/g DM), (+)-catechin (32.82-35.84 µg/g DM), (−)-epicatechin (37.78-45.89 µg/g DM), and myricetin (30.07-35.84 µg/g DM), which were significantly higher in the BWEP produced from GA or MT separately. The study showed that although blending GA and MT has the potential to improve the quality of BWEP, using these biopolymers separately showed a promise to promote a food circular bioeconomy.